THE EFFECTIVENESS OF VILLAGE HEAD POLITICAL COMMUNICATION IN INCREASING THE SUCCESS OF THE CLIMATE VILLAGE PROGRAM: Political Communication, Village Heads, and Climate Village Programs - Hasti Retno Dewi; Tria Patrianti; Fal Harmonis (Yasi Learning Education Research, 2025)
Unstable climate change has the potential to reduce economic growth, food security, and human health. This study aims to explore the effectiveness of political communication of village heads in increasing the success of the Climate Village Program. Qualitative research method with interviews with 30 village heads who have received awards from the National Climate Change Week (PNPI) and content analysis from 30 relevant communication journals. The results of the analysis show that effective political communication plays a role in creating a society that is aware and responsive to environmental issues. The implementation of a good socialization strategy involving all levels of society and information transparency encourages active participation and collaboration, which is essential for the success of the program. The support of community and government leaders, as well as the intensification of communication, is very good for increasing the positive impact on environmental sustainability. The implications of the implementation for other heads of desai that do not include informants are more effective in implementation if there are program challenges that require serious attention, especially in two implementations, namely improving environmental education and infrastructure investment. The results of this study refer to the need for integrated efforts in environmental management and sustainable development.